The Utilization of School Health Unit in Promoting Children's Mental Health in Kelurahan Limo Depok - Evin Novianti; Duma Lumban Tobing (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
School Health Unit (UKS) is conceived to accommodate children's problems, either physically, psychologically, emotionally, morally, or spiritually. However, in its implementation, the majority of UKS in schools tend to handle physical complaints rather than provide more holistic services. The purpose of this commmunity-empowerment activity was to increase the role of nurses in the physical and mental health promotion of school children by examining the UKS role in Elementary State School (SDN) 01 Limo. The community-empowerment activity carried out included the provision of material about growing children both physically and mentally, training parents to communicate assertively with the child by responding positively to the child's emotions. Before the activity was implemented, 60 respondents were measured for their ability to handle the material and the assertive communication. By using the Paired T-test, the result of a significant influence on the improvement of knowledge, attitudes and psychomotor with pvalue = 0,000 (P < 0.05) was obtained. The respondents’ knowledge increase by 6.51 points, psychomotor 5.73 points, and attitude 2.46 points. It was concluded that mental health promotion efforts incorporated in UKS should be continued as the flagship program of SDN 01 Limo.